Effect of pH sodium chloride on the techno-functional properties of residual linseed meal (Linum usitatissimum L.) - Vegas Niño, Rodolfo Moisés (2021)
The present research aimed to evaluate the effect of pH and NaCl on the absorption power of water, gelling, emulsifying and foaming capacity of residual linseed meal (Linum usitatissimum L.). The residual flour (without mucilage) was obtained by boiling the seeds in distilled water, for their subsequent filtration and drying (40 °C x 48 hours) and conversion into flour (type A flour). Whole flaxseed flour was also obtained (without extracting the mucilage) which was called type B flour. The techno-functional properties were determined at pH 3, 5, 7 and 9 as well as at NaCl concentrations of 0.1, 0.25 and 0.5 M. The highest water absorption capacity in type A and B flour was 2.81 and 2.38 g H2O / g solid respectively at pH 5. The oil absorption in type A and B flour was 1.87 and 1.26 g oil / g solid. The highest emulsion in type A flour (45.8%) was obtained at pH 9, while for type B flour (57.97%) at pH 3. In type A flour the gelation was weak from 20% w/w, while in type B flour it was weak from 10% and strong from 16% w/w. The foaming capacity of type A flour was 10.7% and 4.07% in type B flour, both at pH 7.